Konsep dan Implementasi Kurikulum Merdeka pada Pembelajaran Abad 21 di SD 20 Kota Bengkulu - Septiyana, Rindang; Nur Yuli Yanti, Nova; Putri, Regita; Delfero, Haris (Yayasan Darussalam Bengkulu, 2024)
At this time the challenges of the times from the rapid currents of globalization and technology are increasingly challenging. Education has an important role to 2st ICIE: International Conference on Islamic Education play in answering and preparing the current and next generations. Through curriculum development that continues to be carried out is one of the answers to meet the required competencies. The improvement of the curriculum from the 2013 curriculum to the merdeka curriculum is a careful step in responding to this. The learning in merdeka curriculum is specifically designed to give the right to learn independently. The purpose of this study is to describe the concept and implementation of an merdeka curriculum in 21st century learning in elementary school. The implementation of the Merdeka Curriculum at the Sd 20 Kota Bengkulu prioritizes project-based learning in order to realize the Pancasila Student Profile. This is also very relevant to 21st century learning which equips students with the 4C skills needed in responding to the challenges of the times. There are 3 (three) choices in the application or implementation of the independent curriculum (IKM) at the SD / MI level, namely: the Independent Learning Category, the independent category changes and the independent category shares at the grade I and grade IV levels in elementary school starting from the 2022/2023 school year.